L' impérialisme d'aujourd'hui - Texier, Jacques; Bidet, Jacques; Löwy, Michael; Husson, Michel; Salama, Pierre; Achcar, Gilbert (Paris : Presses Universitaires de France (PUF), 1995)
Bibliotheek François Vercammen
Frans
Monografie